Extended-spectrum β-lactamase production and antimicrobial resistance among Enterobacteriaceae causing clinical infections in Africa: a systematic review and meta-analysis (2012–2020) - Getahun Kahsay Abay; Mebrahtu Teweldemedhin Shfare; Teklay Gebrecherkos Teklu; Kibriti Mehari Kidane; Tsega Kahsay Gebremeskel; Atsebaha Gebrekidan Kahsay; Kebede Embaye Gezae; Saravanan Muthupandian; Tsehaye Asmelash Degene (European Journal of Medical Research)
Abstract Background Worldwide, antimicrobial resistance (AMR) has grown to represent a serious threat to the diagnosis, management, and prevention of bacterial diseases. Due to their multidrug resistance attributes, the WHO has classified extended-spectrum-β-lactamase-producing Enterobacteriaceae (ESBL-PE)-associated infections as infections of critical significance, posing a serious risk to human health. Thus, the goal of this systematic review and meta-analysis was to assess the pooled prevalence of ESBL-PE and AMR among strains causing clinical infections in Africa. Methods In this systematic review and meta-analysis, two investigators independently made an electronic search in Google Scholar and PubMed databases using related keywords and corresponding “MeSH.” terms for the PubMed. The accessed studies were screened, assessed for eligibility, and critically evaluated as per the PRISMA guidelines. The prevalence and 95% confidence intervals (CI) for ESBL-PE in Africa were evaluated using a random-effects model of a meta-analysis. As a visual and statistical way assessment, the funnel plot and Egger's test were utilized to assess the risk of bias or publication bias, with a statistically significant level of bias being determined at p < 0.05. Results Twenty-six studies were included in the meta-analysis. Among the included studies done in Africa, the overall pooled proportion of ESBL-PE was reported to be 28% (95% CI 25–31%). ESBL-PE prevalence differed by region, the pooled estimates for East and North Africa were 29% (95% CI 20–38%) and 19% (95% CI 6–33%), respectively. The greatest sub-group analysis of pooled estimates among bacterial isolates was found in Klebsiella. pneumoniae, at 73% (95% CI 62–85%), while Proteus mirabilis had the lowest, at 40% (95% CI 1–81%). Conclusions In Africa, ESBL-PE is noticeably prevalent. The included studies demonstrated a significant variation in ESBL-PE resistance among the countries. This illustrates the necessity of actively monitoring antimicrobial resistance in Africa to develop interventions aimed at halting the spread of ESBL-PE.